Implementasi Kurikulum Merdeka Belajar - Ahmad Zainuri; Yunita Yunita; Ibrahim Ibrahim; Ahmad Zulfi; Mulyadi Mulyadi (Jambura Journal of Educational Management, 2023)
This article discusses the implementation of the independent learning curriculum at the Jami'atul Qurro' Islamic Boarding School in Palembang, with the aim of analyzing how the process of implementing the independent learning curriculum at the Jami'atul Qurro' Islamic Boarding School. This type of research is qualitative with a descriptive approach. The results of this study can be seen that the independent learning curriculum has been implemented, by looking at the essence of the Pancasila Student Profile, namely noble character, global diversity, critical thinking, mutual cooperation, independence and creativity. In the implementation process, it starts from the implementation plan, implementation and evaluation. The planning process is by determining the designs of the independent curriculum and participating in workshops on the independent learning curriculum before implementing the learning curriculum, followed by the implementation process and there is also an evaluation process that is carried out in accordance with applicable regulations. The obstacle to the implementation of the independent curriculum is that when the implementation of the independent curriculum is too early to be implemented and on average it still uses K13 so that the implementation of the curriculum is still followed up in the process of improvement and preparation. Then there must be socialization of the independent learning curriculum also needs to be socialized intensely and as well as possible so that this independent learning curriculum can be carried out properly.